Pengaruh Komunikasi Internal Terhadap Kinerja Karyawan PT.XYZ - Isti Prabawani; Ririn Kusumawati; Andi Miranda (Pusat Riset dan Inovasi Nasional, 2023)
Internal communication that occurs at PT. XYZ will affect work behavior which is indicated by employee performance towards the company. The formulation of the problem in this study is how internal communication influences employee performance at PT. XYZ, how much influence does internal communication have on employee performance at PT? XYZ. The type of research method used in this study is a quantitative method with data collection techniques through questionnaires, literature study, and documentation study. The object of this research is all employees totaling 43 people. The analysis technique used is an instrument test (validity test and reliability test), simple linear regression analysis, F test, and correlation analysis. The results of data analysis show a simple linear regression equation Y = 42.116 + 0.510, which means that for every 1 unit increase in internal communication (X) then the performance (Y) increases by 0.510, with a correlation coefficient value of r = 0.528 meaning that internal communication simultaneously has a moderate effect on employee performance. which is also evidenced by count 15.825 > table of 4.08 with a significance level of 5%, Ho is rejected and Ha is accepted.